Hypothalamic Lipoma: Outcome of an Intracranial Developmental Lesion - Ali Alkhaibary; Noura Alsubaie; Ahoud Alharbi; Noor Alghanim; Laila Baydhi; Sami Khairy; Fahd Musawnaq; Abdulaziz Alarifi; Mohammed Alwohaibi; Ahmed Aloraidi; Makki Almuntashri; Ahmed Alkhani (Case Reports in Surgery)
Background. Hypothalamic lipomas are benign developmental lesions that tend to be discovered incidentally. This article describes the radiological features, outcome, and the postulated theories behind hypothalamic lipomas development. Methods. The electronic archive of neurosurgery was retrospectively reviewed. All patients with a neuroradiological diagnosis of hypothalamic lipoma, between 2005 and 2020, were included. Results. Out of 246 patients with intracranial lipomas, a total of six patients with hypothalamic lipomas have been identified. On computed tomography images, one of the hypothalamic lipomas demonstrated calcification. On magnetic resonance imaging, peripheral enhancement after contrast administration was noted in one of the lesions. Considering the benign nature of the lesions, neurosurgical intervention was not indicated. Conclusion. The majority of patients with hypothalamic lipomas are asymptomatic and undergo brain imaging for other indications. Although uncommon, such developmental lesions can be identified in the general population, especially with the advancement of neuroimaging techniques.